Upaya Menjaga Kesehatan Pada Usia Lanjut Melalui Kartu Yoga di Pusat Pelayanan Keluarga Sejahtera (PPKS) 2022 - Nurasih Nurasih; Endang Nurrochmi; Rani Widiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Yoga practice is beneficial for bodily health, emotional stability and a calm spirit and is a recommended exercise for the elderly. This Community Service aims to improve the health of the elderly through yoga by revitalizing existing programs through modified movements and easier guidance through yoga cards.The activities were carried out at Prosperous Family Service Center for 10 elderly people with age criteria of 50 to 60 years, without physical impairment. This activity also involved elderly cadres in an effort to ensure the continuity of activities at PPKS. The instruments needed are a chair, a 35 cm bamboo stick as a supporting tool in achieving the target organ being trained. Elderly Yoga exercises are carried out once a week for 4 weeks and practice independently at home using yoga cards that have been made by the Community Service Team. At each meeting, the elderly do yoga exercises for a maximum of approximately 60 minutes, blood pressure checks and interviews are carried out regarding complaints felt before and after doing yoga exercises. The results of elderly people with hypertension show a decrease in blood pressure, both systolic and diastolic, and the physical complaints felt by the elderly decrease and even disappear. PPKS should be able to increase the role of existing elderly cadres to be able to further motivate and revive efforts for elderly health programs, one of which is through Elderly Yoga.